Minimising harms of tight glycaemic control in older patients with type 2 diabetes - Wade Thompson (African Journal of Primary Health Care & Family Medicine)
In older adults with type 2 diabetes (T2DM), tight glycaemic control (HbA1c 7%) can result in more harm than benefit, especially when using insulin or sulfonylureas. Older adults are at higher risk for adverse drug events, especially hypoglycaemia, which may cause falls, confusion and hospitalisations. This Therapeutic Letter evaluates the risks of tight glycaemic control in older adults with T2DM, focusing on deprescribing diabetes medications in those over 65, especially those with multimorbidity and polypharmacy. It assesses the evidence from clinical trials and guidelines, with a focus on preventing hypoglycaemia and improving patient-centred care through relaxed HbA1c targets. Large randomised controlled trials show that intensive glycaemic control (HbA1c ≤ 7%) does not reduce cardiovascular risk, but increases hypoglycaemia and mortality, particularly in older adults. Instead, glycaemic targets should be adjusted based on the patient’s overall health and life expectancy. Deprescribing may be considered, starting with drugs most likely to cause hypoglycaemia (sulfonylureas or insulin). Regular reassessment and patient involvement in creating individualised treatment plans are essential.